Penerapan Reward dalam Pembelajaran PAI untuk Meningkatkan Antusiasme Belajar Siswa - Zahra, Obitia Az; Reksiana, Reksiana (Prodi Pendidikan Keagamaan Islam, 2024)
To realize effective and efficient educational goals, teachers must have a way to foster interest in learning in students. One of the ways that teachers can do this is by applying the reward method at school, this reward method is a tangible manifestation of the teacher's efforts in motivating students to foster more interest in learning. The purpose of this study was to determine how the Application of Reward in PAI Learning to Increase Student Learning Enthusiasm at MI Miftahul Huda Muhammadiyah Cinangka Depok. The method used in this research is to use qualitative research, with a descriptive approach. The research results of the Application of Rewards in Islamic Education Learning to Increase Student Learning Enthusiasm at MI Miftahul Huda Muhammadiyah Cinangka Depok show the application of this reward goes well, by the way the teacher gives praise, respect, gifts, and signs of appreciation to the students. Therefore, this reward is very visible from the students' interest in learning when in class, the students are more enthusiastic when participating in class learning, especially in Islamic Religious Education lessons. The challenges faced by teachers at MI Miftahul Huda Muhammadiyah Cinangka Depok are that there are still some students who are lacking in reading, writing, and memorizing.